An Alternative Method of Measuring Area Specific Resistance of Chromia Scales Using Electrochemical Impedance Spectroscopy. Issue 3 (1st March 2023) - Visibile, Alberto; Gagliani, Luca; Ahlberg, Elisabet; Svensson, Jan-Erik; Froitzheim, Jan
Abstract : A novel method that employs electrochemical impedance spectroscopy (EIS) is developed to characterize the oxide scale resistance and thickness of Crofer 22 APU after exposure at 800 °C in humidified air. Crofer 22 APU, is one of the most commonly used materials for solid oxide fuel cell (SOFC) interconnects, an application for which oxide scale resistance is of paramount importance. The kinetics of oxide growth were studied for up to 6, 000 h using three different techniques: electron microscopy of cross-sections, gravimetry, and EIS capacitance measurements of the oxide scale. EIS was used to evaluate the scale thickness starting from the material capacitance, and the material resistance at high temperature was estimated using extrapolation of the impedance values at room temperature. The result obtained with this novel EIS method are comparable to those obtained using conventional techniques, and in addition, the new method is cheaper, faster, and more reliable. Moreover, it enables repetitive exposures of the same sample without altering the specimen properties.